14. ANALYSIS OF FACTORS RELATED TO POSTPARTUM DEPRESSION AT NATIONAL HOSPITAL OF OBSTETRICS AND GYNECOLOGY (Vietnam Journal of Community Medicine, 2023)
Objective: To analyze factors related to postpartum depression (PPD) in pregnant women givingbirth at the National Hospital of Obstetrics and Gynecology. Methods: This is a descriptive studyon 550 pregnant women giving birth at the National Hospital of Obstetrics and Gynecology in 2020-2021. Results: The maternal age group under 25 has a 5.84 times higher risk of PPD than the agegroup 25-34 (95% CI: 3.21-9.27). Unmarried women have an 11.32 times higher risk of PPD thanmarried women (95% CI 4.64-20.1). Paying attention to the sex of the child also increases the risk ofPPD by 2.73 times. Babies born before 37 weeks and weighing less than 2500g increase the risk ofPPD by 4.69 times (95% CI 1.13-195) and 2.24 times (1.05-8.41), respectively. After birth, babiescrying at night also increased the risk of PPD by 4.42 times (95% CI 1.6-12.3). The relationshipbetween husband and wife is not in harmony is also a risk factor for increasing the rate of PPD.Conclusion: Non-reproductive maternal age, singleness, and farming mothers are individual factorsthat increase the risk of postpartum depression. Low birth weight (
Keywords: Postpartum depression, related factors, National Hospital of Obstetrics and Gynecology.